PENGARUH BERBAGI PENGETAHUAN DALAM PERENCANAAN KARIR TERHADAP EFIKASI DIRI PARA PENCARI KERJA DALAM MEMBUAT KEPUTUSAN KARIR - , Eko Imam Santosa; , Drs. Fathul Himam, M.Psi., MA., Ph.D., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Every year more and more graduates from university becoming job seekers, it is not rare for a university graduate to be unemployed. Difficulty in finding work often occurs because the graduates do not have a good career planning so that individuals do not have a clear career direction. The purpose of this experimental study was to determine the effectiveness of knowledge sharing in career planning to increase career decision making self-efficacy of job seekers. Subjects were 57 people subject, 30 subjects were in the experimental group and 27 were in the control group. The criteria of subjects is a graduation degree with 0 to 3 years old who has a low, medium or high CDSE score. The experimental group will receive manipulation, the other group was a waiting list for the next batch and data was not analized. Data analysis was performed using mixed anova. The results of data analysis showed that career planning using knowledge sharing methods was statistically proven to improve career decision making selfefficacy of job seekers (F = 22.736, p <0.00). Findings and suggestions for other researchers are discussed further.